Investment Decision Making on Small-sized Enterprise: Case of the Aquaculture Fishery in Tuban Regency - Utami, Tiwi Nurjannati; Subagyo, Subagyo (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2024)
This study aims to analize the meaning, the decision making and the identification of fishery small entreprise investment. The study locates in Tuban Coastal–East Java Indonesia. It employs qualitative methods with case study. The data are collected through semi-structural interview, observation, and documentation. Techniques and time triangulation are used to check the validity of the data. CV. SAM is a fishery business on aquaculture of shrimp (vanname sp) and catfish (clarisas batracus sp), also makes probiotic and vitamins for fishes. The result shows that the entrepreneur interprets an investment as purchasing an asset to operation the entreprise. The owner decides on an investment for the purpose of expanding business and taking opportunity on the potential big market. Nevertheless, the enterprise identification several risks on their business. Firstly, operational risk; there are fish disease and increasing price of the feed and medicine on vanname that decreasing profit. Secondly, market risk; there are rejection or decline of selling price if the quality on low standart especilly for vanname on foreign markets. The entreprise anticipates operational risk by producing probiotics and vitamins for fish. On the market risks, the entrepreneur hasn’t any action to anticipate and to find solution especially for vanname. To develop the fishery small enterprise, the stakeholders need to support them in getting solution.